The Denotation of Socio-Political Infantilism in the Context of RA Democratization - Dumanyan, Sona (Տիգրան Մեծ)
The primary goal of this article is to highlight the connection between socio-political infantilism and civic subject culture. Some realities of Armenian family life contributing to the occurence of socio-political infantilism are discussed. The analysis of the results of the research done by the indepth interview method confirmed that social infantilism makes political infantilism inevitable and subject culture is a consequence of socio-political infantilism. Thus, it also be-comes clear that socio-political infantilism is an unfavorable factor in democratization processes.
Keywords: Social philosophy